Prostate Cancer Risk Stratification in Men With a Clinical Suspicion of Prostate Cancer Using a Unique Biparametric MRI and Expression of 11 Genes in Apparently Benign Tissue: Evaluation Using Machine‐Learning Techniques. Issue 5 (6th October 2019) - Montoya Perez, Ileana; Jambor, Ivan; Pahikkala, Tapio; Airola, Antti; Merisaari, Harri; Saunavaara, Jani; Alinezhad, Saeid; Väänänen, Riina‐Minna; Tallgrén, Terhi; Verho, Janne; Kiviniemi, Aida; Ettala, Otto; et al.
Abstract : Background: Accurate risk stratification of men with a clinical suspicion of prostate cancer (cSPCa) remains challenging despite the increasing use of MRI. Purpose: To evaluate the diagnostic accuracy of a unique biparametric MRI protocol (IMPROD bpMRI) combined with clinical and molecular markers in men with cSPCa. Study Type: Prospective single‐institutional clinical trial (NCT01864135). Subjects: Eighty men with cSPCa. Field Strength/Sequence: 3T, surface array coils. Two T2 ‐weighted and three diffusion‐weighted imaging (DWI) acquisitions: 1) b‐values 0, 100, 200, 300, 500 s/mm 2 ; 2) b‐values 0, 1500 s/mm 2 ; 3) b‐values 0, 2000 s/mm 2 . Assessment: IMPROD bpMRI examinations were qualitatively (IMPROD bpMRI Likert score) and quantitatively (DWI‐based Gleason grade score) prospectively reported. Men with IMPROD bpMRI Likert 3–5 had two targeted biopsies followed by 12‐core systematic biopsies (SB); those with IMPROD bpMRI Likert 1–2 had only SB. Additionally, 2‐core from normal‐appearing prostate areas were obtained for the mRNA expression of ACSM1, AMACR, CACNA1D, DLX1, PCA3, PLA2G7, RHOU, SPINK1, SPON2, TMPRSS2‐ERG, and TDRD1 measured by quantitative reverse‐transcription polymerase chain reaction. Statistical Tests: Univariate and multivariate analysis using regularized least‐squares, feature selection and tournament leave‐pair‐out cross‐validation (TLPOCV), as well as 10 random splits of the data in training‐testing sets, were used to evaluate the mRNA, clinical and IMPROD bpMRI parameters in detecting clinically significant prostate cancer (SPCa) defined as Gleason score ≥ 3 + 4. The evaluation metric was the area under the curve (AUC). Results: IMPROD bpMRI Likert demonstrated the highest TLPOCV AUC of 0.92. The tested clinical variables had AUC 0.56–0.73, while the mRNA and additional IMPROD bpMRI parameters had AUC 0.50–0.67 and 0.65–0.89 respectively. The combination of clinical and mRNA biomarkers produced TLPOCV AUC of 0.87, the highest TLPOCV performance without including IMPROD bpMRI Likert. Data Conclusion: The qualitative IMPROD bpMRI Likert score demonstrated the highest accuracy for SPCa detection compared with the tested clinical variables and mRNA biomarkers. Level of Evidence: 1 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020;51:1540–1553.